Co‐location of Addiction Liaison Nurses in Three Quebec City Emergency Departments: Portrait of Services, Patients, and Treatment Trajectories. Issue 3 (September 2016) - Blanchette‐Martin, Nadine; Tremblay, Joël; Ferland, Francine; Rush, Brian; Garceau, Pascal; Danielson, Anna‐Marie
ABSTRACT: N/A: Many people coming to emergency departments (EDs) or receiving other hospital services arrive with an unidentified substance use disorder (SUD). A well‐supported approach to reach these patients is the co‐location of an addiction liaison nurse (ALN) in the ED or other hospital departments in order to facilitate case identification and linkage to treatment. Objectives. : The aim is to describe the patients identified by ALNs and their subsequent treatment trajectories. Method. : Monitoring of 1, 482 patients who represented 2, 082 service requests addressed to the ALNs by other hospital professionals, and who were assessed by the ALNs in three Quebec City hospitals (monitoring period varying between 6 to 24 months). Results. : Based on the total service requests, the trajectories can be summarized as follows: going forward from the initial request to: 1) an ALN assessment (89.7% of initial requests), 2) a referral to an addiction program (78.0% of initial requests), 3) attendance at a specialized addiction assessment (50.0% of initial requests), and 4) participation in one or more treatment activities after specialized assessment (41.1% of initial requests). Of those who participated in the specialized addiction program, 88.4% had no active file in the centre, representing 44.2% of the initial ALN requests. Conclusions. : ALN practice in an ED successfully meets the objective to redirect known clients and attract new clients to addiction treatment programs. Interesting differences were observed between hospitals that indicate efficacy variations based on the particular organization of hospital services and the type of patients coming from the local neighbourhood. Abstract : N/A: Beaucoup de gens qui viennent aux services d'urgence (SU) ou recevant d'autres services hospitaliers arrivent avec un trouble non identifié d'utilisation de substances (TUS). Une approche très reconnue pour atteindre ces patients est la localisation d'une infirmière de liaison en soin de dépendance (ILD) aux SU ou autres services de l'hôpital, afin de faciliter l'identification des cas et la liaison pour le traitement. Objectifs. : Le but est de décrire les patients identifiés par les ILDs et leurs parcours de traitement subséquent. Méthode. : Suivi de 1 482 patients qui ont présenté 2 082 demandes de service adressées aux ILDs par d'autres professionnels de l'hôpital, et qui ont été évalués par les ILDs dans trois hôpitaux de la ville de Québec (période de surveillance variant entre 6 à 24 mois). Résultats. : Basé sur le total des demandes de service, les parcours peuvent être résumées comme suit: aller de l'avant à partir de la demande initiale à: 1) une évaluation de l'ILD (89, 7% des demandes initiales), 2) une recommandation à un programme de la toxicomanie (78, 0% des demandes initiales ), 3) la participation à une évaluation de la toxicomanie spécialisée (50, 0% des demandes initiales), et 4) la participation à une ou plusieurs activités de traitement après une évaluation spécialisée (41, 1% des demandes initiales). Parmi ceux qui ont participé au programme spécialisé en toxicomanie, 88, 4% n'avaient pas de fichier actif au centre, ce qui représente 44, 2% des demandes d'ILDs initiales. Conclusions. : La pratique de l'ILD dans un SU répond avec succès à l'objectif de rediriger les clients connus et attirer à des programmes de traitement de nouveaux clients souffrant de dépendance. Des différences intéressantes ont été observées entre les hôpitaux qui indiquent des variations d'efficacité en fonction de l'organisation particulière des services hospitaliers et le type de patients provenant du quartier environnant.